2019
DOI: 10.1021/jacs.9b09942
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Separation of 1-Butene from 2-Butene in Metal–Organic Frameworks with Open Metal Sites

Abstract: Most C 4 hydrocarbons are obtained as byproducts of ethylene production or oil refining, and complex and energyintensive separation schemes are required for their isolation. Substantial industrial and academic effort has been expended to develop more cost-effective adsorbent-or membrane-based approaches to purify commodity chemicals such as 1,3-butadiene, isobutene, and 1-butene, but the very similar physical properties of these C 4 hydrocarbons makes this a challenging task. Here, we examine the adsorption be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 53 publications
0
35
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7] In contrast, butene separation (and associated coordination chemistry) has received relatively little attention because butene/butane distillation columns operate around ambient temperature, requiring relatively less intensive engineering, and the relatively small size of the global butene market, which is in the low billions of dollars. [8][9][10] As with lighter olefins, separation methods based on butene-adsorption have been investigated as potentially more energy-efficient, replacement for distillation. [8,[11][12] Butene-adsorption methods are mainly focused on the use of zeolites [13][14][15] and metal-organic frameworks (ESI Section 1.1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] In contrast, butene separation (and associated coordination chemistry) has received relatively little attention because butene/butane distillation columns operate around ambient temperature, requiring relatively less intensive engineering, and the relatively small size of the global butene market, which is in the low billions of dollars. [8][9][10] As with lighter olefins, separation methods based on butene-adsorption have been investigated as potentially more energy-efficient, replacement for distillation. [8,[11][12] Butene-adsorption methods are mainly focused on the use of zeolites [13][14][15] and metal-organic frameworks (ESI Section 1.1).…”
Section: Introductionmentioning
confidence: 99%
“…[8,[11][12] Butene-adsorption methods are mainly focused on the use of zeolites [13][14][15] and metal-organic frameworks (ESI Section 1.1). [8,16] These studies have shown success using flexible frameworks for size discrimination [17] and π-coordination, including those involving Cu(I) and Cu-(II) [10,15,[18][19][20][21][22][23][24] for the separation of butene isomers [9,25] and 1,3butadiene from other C 4 hydrocarbons. [26] Non-porous small molecule adsorbents are an emerging class of materials that can overcome the traditional trade-offs between selectivity vs capacity and selectivity vs heat of adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…The sandwich‐shaped macrocycle [ 1 2 Ag 6 L n ] 6+ is concentrically aligned to form a large channel in the crystal (Figure 3c). Thus, the crystal could be used for molecular capture inside the pore utilizing coordination bonds with metals on the inner wall [43–45] …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the crystal could be used for molecular capture inside the pore utilizing coordination bonds with metals on the inner wall. [43][44][45]…”
Section: Resultsmentioning
confidence: 99%
“…Metal-Organic Framework (MOF) materials have long been recognised as promising candidates for a wide range of applications including, but not limited to, CO 2 storage, [1][2][3] separations [4][5][6][7] and electrocatalysis. [8][9][10][11] In the field of gas sorption, [12][13][14] storage and crude separations, 7,[15][16][17] the MOF-74/CPO-27 material, 12 ([M 2 (dobdc)], where M 2+ = Mg, Mn, Fe, Co, Ni, Cu and Zn and dobdc 2-= 4,6-dioxido-1,3-benzenedicarboxylate), enjoys significant attention due to its porosity and ultra-high concentration of open metal sites that facilitate relatively strong guest binding compared with typical physisorption in framework materials. 18 One attractive means by which multifunctional properties within a MOF may coexist or be tuned (such as gas sorption or selectivity) is by use of a redox 'switch', where certain characteristics emerge as a result of oxidation or reduction.…”
Section: Introductionmentioning
confidence: 99%